Meta-Analysis of the Relationship between the APOE Gene and the Onset of Parkinson’s Disease Dementia - Suisui Pang; Jia Li; Yingyu Zhang; Jiajun Chen (Parkinson's Disease)
Purpose. To clarify the relationship between certain genotypes or alleles of the APOE gene and the onset risk of Parkinson’s disease dementia (PDD). Methods. The PubMed, Cochrane, Embase, CBM, CNKI, and Wanfang databases were searched to identify all case-control studies and cohort studies published before October 30, 2017, that investigated the association between the APOE gene and the onset of PDD. Manual information retrieval was also performed. All studies that met the quality requirements were included in a meta-analysis performed using RevMan 5.3 software. Results. The meta-analysis included 17 studies, with a total of 820 patients in the PDD group and 1,922 in the non-PDD group. The influence of the APOE gene on PDD onset was analyzed from three aspects: five genotypes vs. ε3/3, ε2+/ε4+ vs. ε3/3, and ε4+ vs. ε4−. The risk factors for PDD may include the genotypes ε3/4 (OR 1.47, 95% CI 1.14–1.89) and ε4/4 (OR 2.93, 95% CI 1.20–7.14). In patients with PDD, there was no significant difference in the distribution of ε2+ vs. ε3/3 (OR 1.35, 95% CI 0.97–1.87, P=0.07). The risk of PDD was 1.61 times greater in ε4+ compared with ε3/3 (OR 1.61, 95% CI 1.24–2.08, P=0.0003). As the results indicated that ε2+ did not play a role as a risk factor or a protective factor, we divided the population into ε4+ and ε4− for the meta-analysis and found that, among patients with Parkinson’s disease, the dementia risk of those with ε4+ was 1.72 times greater than that of those with ε4− (OR 1.72, 95% CI 1.41–2.10, P<0.00001). Subgroup analysis in accordance with different geographical regions revealed that ε4+ was a risk factor for PDD in people from all regions. Conclusions. Among the APOE genotypes, ε2+ is neither a risk factor nor a protective factor for PDD, while ε4+ is a risk factor for PDD. The present results are applicable to Asian, European, and American patients with Parkinson’s disease. Regarding the single APOE genotypes, ε3/4 and ε4/4 may be risk factors for PDD; however, further studies with large sample sizes are needed to verify this.